Exploring the relationship between sexual risk behaviours and HIV Status awareness among men in South Africa: analysis of data from the 2017 South African National house-based HIV prevalence, incidence and behaviour survey - Nhlabatsi, Zanele (Department of Public Health and Family Medicine, 2026)
South Africa has one of the highest HIV prevalence rates globally, with men being a key population at risk due to risky sexual behaviours and lower HIV status awareness compared to women. This study explored the relationships between sexual risk behaviours and HIV status awareness among 1,630 sexually active South African men (≥15 years, median age 34 years, interquartile range 24-44) using data from the 2017 South African National House-based HIV Prevalence, Incidence, and Behaviour Surveys (SABSSMV). Overall, 13.5% of men self-reported living with HIV (srHIV+) and there was high concordance between self-reported and laboratory confirmed HIV status with 92.0% (95% confidence interval [CI] 84.1% - 96.1%) and 88.0% (95% CI 85.5% - 90.2%); p<0.001, of men srHIV+ and those self-reporting not living with HIV (srHIV-) being laboratory confirmed, respectively. In total, 68.3% (95% CI 64.6% - 71.8%) of men reported casual sexual partners ( 48.2% [95% CI 39.0% - 57.5%] among men srHIV+ vs. 71.4% [95% CI 67.4% - 75.2%] among men srHIV-); p<0.001, 4.9% (95% CI 3.6% - 6.7%) reported ≥2 sexual partners (2.6% [95% CI 1.1% - 6.2%] vs. 5.3% [95% CI 3.8% - 7.4%]); p = 0.116, 26.5% (95% CI 23.4% - 29.9%) reported inconsistent condom use at last sex with all partners in the past year (23.3% [16.0% - 32.7%] vs. 27.0% [95% CI 23.6% - 30.8%]); p = 0.430, and 14.2% (95% CI 11.8% - 17.1%) reported alcohol use at last sex (16.9% [95% CI 10.9% - 25.1%] vs. 13.8% [11.3% - 16.9%]); p = 0.431, with values in brackets showing the proportion among those (srHIV+) versus (srHIV-), respectively. In logistic regression models, men (srHIV+) were less likely to report engaging in casual sex compared to men (srHIV-) ( (adjusted odds ratio 0.51 95% CI: 0.27–0.97). Variations in sexual risk behaviours were observed by demographic characteristics, and age appeared to modify the association between reported HIV status and some risk behaviours. The findings highlight the impact of HIV status on risky sexual behaviour, emphasizing the need for comprehensive HIV testing and counselling (HTC), safe sex education, and integrated behavioural and structural approaches in healthcare. Tailored interventions such as age-specific messaging, accessible educational content, ensuring condom and PrEP availability, youth-friendly tech-based solutions like online counselling or mobile apps, and public campaigns promoting safe sexual practices, will be essential to address the unique needs of different age groups, education levels, HIV statuses, and geographic settings.